The Effect of Farmer Group Dynamic on the Income of Red Branches in Indonesia - Kusmana, Endang; Adelin, Dessy; Andriana, Susan (International Journal of Economics and Financial Issues, 2019)
The purpose of this study was to know influence of Farmer Group Dynamic on the income of red chili farming. The method used in this study is mixed methods. A quantitative method using a sample of 83 respondents, while the qualitative method uses 20 informants for interviews and 9 informants for FGD. Based on the results of the analysis, it was found that Farmer Group Dynamic had a positive and significant effect on the income of the Red Chili farm, so that if the Farmer Group Dynamic activity is carried out properly, on target, and appropriately benefits the farmers, then the business income of the Red Chili farmer will increase, which includes production per planting season for members in carrying out Red Chilli farming that is active in the group, the selling price of the product per planting season for members in carrying out the red chili farming that is active in the group, and the income per planting season for members in carrying out the active red chili farming in the group. Farmer group dynamics have a positive and significant effect on the income of the Red Chili farm. So that farm income can be determined by the dynamics of farmer groups that have a purpose, have a function, carry out coaching and group development, group cohesiveness, and group effectiveness. Keywords: Farmer group dynamic, Farmer Group Dynamics, Farmer Income JEL Classifications: Q12, Q13, Q18 DOI: https://doi.org/10.32479/ijefi.7619